METHODOLOGY FOR USING DIGITAL TOOLS IN ACADEMIC WRITING AND SCIENTIFIC RESEARCH - Toreeva Azima Tazabay qizi (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The development of digital technologies has significantly influenced academic writing, offering both advantages and challenges. This study examines the role of digital tools in supporting the writing process across different stages. The findings show that most tools are effective in improving grammar and vocabulary, while fewer address higher-level skills such as argumentation and text organization. The study also reveals differences in how professionals use these technologies, ranging from extensive integration to limited use. In addition, collaborative platforms play an increasingly important role in research communication. Overall, the study emphasizes the need for more effective and structured use of digital tools to enhance academic writing practices.